Pengaruh Penggunaan Absensi Sidik Jari (Fingerprint) dan Pemberian Hukuman (Punishment) Terhadap Kedisiplinan Siswa - Imam Azhar (Darajat: Jurnal Pendidikan Agama Islam, 2018)
The problem in this research is (1) Whether the use of a fingerprint directly effect senstencing giving punishment, (2) Whether the use of fingerprint directly effect on the discipline, (3) Whether the giving punishment directly effect the discipline (4) Whether the use of fingerprint attendance indirect effect on discipline throuht punishment. The population in this research were all students at MA TABAH Kranji totaling 994 students.. To determine the number of samples to be taken in this research, researchers used Taro Yamane formula in order to obtain 90 students to use as a sample. Sampling technique used in this research is to use the technique of questionnaires and documentation. The results of hypothesis testing using SPSS 16.0 for windows is known that: ( 1 ) the use of a fingerprint directly influence sentencing. This is shown in the results of the analysis on the significance test t count > t table (11,59 >1,987) and the P value (0,000< 0,05). ( 2 ) the use of a fingerprint directly affect student discipline. This is shown in the results of the analysis on the significance test test t count > t table (13,59 >1,987) and the P value (0,000> 0,05). ( 3 ) giving punishment directly affect student discipline. This is shown in the results obtained by the analysis of the significance test t count > t table (13,93 >1,987) and the P value (0,000<0,05). ( 4 ) the use of fingerprint indirect effect on student discipline is 38,44%.